Reactivity of the Bioactive Aminodiol Subunit: Experimental and Theoretical DFT Study of the Reaction of Silyl Protected Anti-N-Boc-3-Amino-3-Phenyl-1,2-Propanediols with NaH - Hamdach, Abdelkrim; Bentama, Abdeslem; Gil, Salvador; Zaballos-Garcia, Elena; Sepulveda-Arques, Jose; Jose Zaragoza, Ramon (Letters in Organic Chemistry, 2006)
The reaction of the partially protected (TBDMS), anti-N-Boc-3-methylamino, or anti-N-Boc-3- amino-3-phenyl-1,2-propanediols 7a or 7b, with sodium hydride, yields the oxazolidinones 8 and the silyl migration oxazinones 9, with different ratios (8a:9a; 93:7 and 8b:9b 50:50). The results, have been explained experimental and theoretically by kinetic control of the reaction.
Keywords: oxazinone